Cholesteryl Ester Storage Disease – A Rare Presentation (Journal of Medicine, 2018)
Cholesteryl Ester Storage Disease (CESD) is a rare genetic disease characterized by accumulation of cholesteryl esters and triglycerides in many tissues due to deficiency of Lysosomal Acid Lipase (LAL/ LIPA) enzyme, which is essential for hydrolysis of triglycerides and cholesterol esters in lysosomes.1 The diagnosis is indicated by abnormal lipid profile, deposition of cholesterol crystals in internal organs and reduced acid lipase activity in leukocytes. Here we report a 16 year-old girl who presented with repeated episodes of hepatic encephalopathy with onset of first symptom at 9 years of age with history of consanguinity of marriage between parents. On examination, we found hepatosplenomegaly. Laboratory examination showed abnormal lipid profile and reduced activity of acid lipase enzyme in leukocytes. After exclusion of other possible pathological conditions and on the basis of lab criteria, we diagnose the case as Cholesteryl Ester Storage Disease (CESD).J MEDICINE JUL 2018; 19 (2) : 130-132